THE CHALLENGES FACED BY TEACHERS IN IMPLEMENTING CHARACTER EDUCATION IN SCHOOLS AT SMP DDI POLMAN SULBAR - Hiljati, Hiljati; Naro, Wahyuddin; Syamsudduha, Syamsudduha; Rahman, Ulfiani; Muslimin, Muslimin (Yayasan Education and Social Center, 2024)
This study aims to identify challenges in implementing character education at SMP DDI Polman, West Sulawesi. Character education in this school is expected to shape students with excellent and responsible behavior. Nevertheless, it encounters a variety of challenges during its execution. This investigation implements a qualitative descriptive methodology. Data were gathered through documentation analysis, direct observation, and in-depth interviews. The study results indicate that one of the main obstacles is the limited time available in the learning schedule. Character education is often considered an additional, low priority because the main focus is more on the academic achievement being tested. In addition, the lack of understanding and commitment from all related parties, including teachers, principals, and students, also affects the effectiveness of the implementation of character education. Consequently, it is imperative to incorporate character education into all school activities consistently. This study implies that creating a quality generation is contingent upon enhancing collective awareness of the urgency of character education and improving time management